Isolation and characterization of thermophilic bacteria for self-healing concrete / Normy Idayu Esahak Ayub ... [et al.] - Esahak Ayub, Normy Idayu; Mohd Saman, Hamidah; Yunus, Balqis; Rahmat, Mohamad Nidzam (UiTM Press, 2022)
Microbial Induced Calcite Precipitation (MICP) derived from certain types of bacteria such as Bacillus sp. as crack healing agent in cementitious materials has been proven in previous works. The effect of bacteria-based self - healing agent application on mortar was studied to clarify possible applicability and benefit. This research paper describes the isolation and cultivation of bacteria, identification of bacteria species, creation of crack, injection of crack with bacteria solution and quantification of healing efficiency of Bacillus sp. (N7) and Bacillus sp. (N10). Besides that, different concentrations of Bacillus sp. N7 and Bacillus sp. N10 were injected into different size of crack openings in mortar samples. Bacillus sp. N7 and Bacillus sp. N10 were identified as Areurinibacillus Thermoaerophilus using 16sDNA identification and the size of the amplicons were 1500 bp. According to the data, the self-healing pattern does not always occur at the highest bacterial concentration. The best production of calcite is achieved at OD600 1.0 for B. subtilis (N7) and Bacillus sp. (N10). XRD analysis showed that Bacillus sp. N7 and Bacillus sp. N10 could form calcite and vaterite phases, which were the major elements of calcium carbonate. From the observation, the variable calcite precipitation on cracks opening of mortar specimens at varying levels of bacterial concentrations is the explanation for the presence of the optimal bacterial concentration for a given bacterial type and mortar mix.